The Effect Of Foot Soak Therapy Using Warm Water On Reducing Blood Pressure In Hypertension Patients - Kristine Dareda; Dian P. Iman; Muhammad Wahyu Wicaksana (Sean Institute, 2023)
Hypertension is a condition in which a person will experience an increase in systolic blood pressure above normal ≥140 mmHg and diastolic ≥90 mmHg. Hypertension can be caused by poor diet and lack of physical activity. The purpose of this research was to find out the effect of foot soak therapy using warm water on lowering blood pressure in patients with hypertension in Malendeng Village, Manado City. This research is a pre experiment research with One Group pretest-postest design. The sampling technique is purposive sampling. The samples amounted to 12 people who had previously checked their blood pressure using a sphygmomanometer. Furthermore, the collected data was tested for data normality. The hypothesis was tested with the Wilcoxon to find out the decrease in blood pressure in respondents with a level of significance (α) 0.05. The results showed that the most common gender obtained in the study was female with 9 respondents (75.0%). The conclusion in this research is that there is an effect of foot soak therapy using warm water on reducing systolic and diastolic blood pressure in patients with hypertension p=0.002. This p value is less than the value of α=0.05.